Health is wealth : health progrmme - Mackenzie, James; Haldane, William S. ([Scotland : Industrial Health Education Council], 1926)
1926 1926 1920s 16 pages CONSTITUTION. 1. The title of the organisation shall be "Industrial Health Education Council." 2. The object of the Council shall be to arrange lectures or other instruction to industrial workers on health subjects, and any other lines of activity in Industrial Health Education which may be approved of by two-thirds of the members of the Council present at a general meeting of the Council. 3. The Council shall consist of President, Vice-Presidents, Chairman, Vice-Chairman, Hon. Treasurers, and General Secretary; with them members elected from subscribers, the medical profession, and from industrial workers. The Council shall have power to invite representatives from the following bodies, viz :- Chambers of Commerce (2); Scottish Trade Union Congress (2); National Health Insurance Committees (2); Friendly Societies (2); Scottish Board of Health (2); Lanarkshire, Fife, Lothians, Ayrshire Miners' Welfare District Committees (1 each); and from other organisations which support public health purposes. (a) The Council shall have power to add to its numbers. (b) The Council shall have power to elect an Executive, if development of the work renders this necessary. (c) Seven members shall form a quorum at all meetings of Council. 4. The members of Council as at 11th July, 1925, shall hold office for three following years, and at the end of the third year one-third shall retire, a third retiring each year thereafter, those retiring in any year being eligible for re-election. 5. The work of the Council shall be maintained by voluntary support. 6. The Council shall meet in February, April, July and October, beginning February, 1926, in Edinburgh and Glasgow in rotation, and on ten days' notice being given to members. The Council shall cause Accounts to be prepared annually, and made up to 31st December in each year. These Accounts, after audit, shall be submitted at the Annual Meeting of the Council and subscribers to be held in February of each year. 7. The Annual Meeting of the Council and subscribers shall be held in February, on the same day and at the same place as the Council meeting for February. At this Annual Meeting reports of work, financial statement, and Secretary's report, shall be submitted for approval, and any other business necessary discharged, and the Council for the ensuing year elected, subject to provision in No. 4. The Council shall have power to fill any vacancies which occur during its term of office. 8. The Council shall appoint such Commitees as may be found necessary. 9. Extraordinary meeting of the Council shall be called on the written requisition of ten members, and this requisition shall be sent to the General Secretary, stating the business to be discussed, fourteen days prior to date of meeting. 10. The Council shall appoint a Finance Committee, consisting of six of its members, a Programme Committee of three, and a Chairman's Committee of four, for consultative purposes and to deal with any matters of urgency which may arise between meetings of Council. The Committees to have power to add their number. 11. The services of all members of Council shall be voluntary, except in the case of the General Secretary, who shall not have voting power. 12. The services of those taking part in the Council's programme of work, e.g., lectures on health subjects, shall be voluntary, subject to travelling and out-of-pocket expenses where desired. 13. In the event of the trades and industries in England and Wales being opened up for the Council's work, a Council shall be elected there, with the same powers as in Scotland, and both Councils shall have three representatives on each other's Council. The two Council shall hold a joint annual meeting in Scotland and England alternately, at such place as may be determined by the Joint Council, and at which reports of the work shall be submitted, with financial statement as in No. 7. 14. Each Council shall be responsible for funds for the work in its own area. In the event of monies given to the work in general and covering both Councils, such monies shall be allocated by the Chairman's Committees of both Councils and reported upon. 15. Alteration in the Constitution shall only be made at the Annual Meeting of the Council, and notice of motion to this effect must be sent to the General Secretary twenty-one days before the date of meeting. 200/B/3/2/C693/1/48